Demonstration of cavitary legionnaires’ pneumonia in a renal transplant recipient - Som Singh, MD; Sylvestre Pineau, BS; Gautam Sikka, MD (Radiology Case Reports)
Legionella pneumophila is a potentially life-threatening infection, especially for individuals with compromised cell-mediated immunity. Typical chest CT findings include multilobed or multisegmented consolidations and ground-glass opacities, but cavitary lesions are rare. This case report details a 29-year-old male renal transplant recipient who developed cavitary Legionnaires' pneumonia. His medical history includes focal segmental glomerulosclerosis and recurrent FSGS post-transplant, managed with a complex immunosuppressive regimen. Following an acute episode of allograft dysfunction treated with alemtuzumab, he developed respiratory symptoms, and initial diagnostics revealed Legionella pneumophila. Despite initial improvement, he presented with worsening symptoms and was readmitted where CT scans indicated necrotizing pneumonia with cavitary lesions. This case highlights the need for vigilant monitoring and tailored therapeutic strategies in immunocompromised patients with Legionnaires' disease.